The platform will undergo maintenance on Sep 14 at about 9:30 AM EST and will be unavailable for approximately 1 hour.
2009
DOI: 10.1093/njaf/26.1.35
|View full text |Cite
|
Sign up to set email alerts
|

Forest Landowners' Willingness to Sell Carbon Credits: A Pilot Study

Abstract: Sequestered carbon is a new forest product that could help private forest owners earn financial returns while keeping their forests intact. Private forest owners are responsible for 78% of forests in Massachusetts, and the carbon these trees sequester could be traded in emerging cap-and-trade carbon markets in the United States. In forming policy about climate change and forestry, it is important to understand the factors that influence the likelihood of landowners choosing to sell sequestered carbon and parti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
28
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(33 citation statements)
references
References 0 publications
4
28
0
Order By: Relevance
“…Additionally, several landowner characteristics were found not to be significant predictors of participation. Although landowners with a long land tenure were not found to be significantly less interested in participating as hypothesized, some other studies have also found length of ownership to not influence participation in carbon programs (Fletcher et al 2009;Thompson and Hansen 2012). Familiarity with managing forests for carbon was also not found to be a significant predictor of participation.…”
Section: Unexpected Findingsmentioning
confidence: 68%
See 2 more Smart Citations
“…Additionally, several landowner characteristics were found not to be significant predictors of participation. Although landowners with a long land tenure were not found to be significantly less interested in participating as hypothesized, some other studies have also found length of ownership to not influence participation in carbon programs (Fletcher et al 2009;Thompson and Hansen 2012). Familiarity with managing forests for carbon was also not found to be a significant predictor of participation.…”
Section: Unexpected Findingsmentioning
confidence: 68%
“…Previous studies on carbon programs and incentive programs for other ecosystem services suggest that payment amount and contract length are important program characteristics and were included in the model. Several studies have demonstrated a positive relationship between the payment amount offered and participation (Dickinson et al 2012;Fletcher et al 2009;Kilgore et al 2008a;Kline et al 2000;Layton and Siikamäki 2009;Markowski-Lindsay et al 2011;Miller et al 2012;Rabotyagov and Lin 2013;Sullivan et al 2005). Payment amount (PAYMENT) was therefore hypothesized to have a positive effect on participation.…”
Section: Model Developmentmentioning
confidence: 99%
See 1 more Smart Citation
“…The United Nation’s REDD program as well as recent proposals in the United States for a carbon offset market are examples of such programs. Broadly speaking, they aim to promote conservation by placing a monetary value on the carbon sequestration services provided by healthy ecosystems [4], [5], [6].…”
Section: Introductionmentioning
confidence: 99%
“…This has often been identified as an important factor in the previous literature (e.g. Horne 2006;Fletcher et al 2009;Markowski-Lindsay et al 2011;Miller et al 2012;Dickinson et al 2012;Håbesland et al 2016;Latta et al 2016;Khanal et al 2017). However, the forest owners had doubts about whether the compensation fully covers the costs of participation or the lost income from timber sales.…”
Section: Discussionmentioning
confidence: 93%